2006
DOI: 10.3346/jkms.2006.21.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Immunohistochemical Staining of p53, bcl-2, and Ki-67 in Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) is one of the most fatal cancers in humans and many factors are known to be related to its poor prognosis. Immunohistochemical (IHC) stainings were done on SCLC specimens in order to investigate the prognostic value of the apoptosis-related gene expression and the tumor proliferative maker, and the relationships among these IHC results and patients clinical characteristics, chemoresponsiveness, and survival were analyzed. The medical records of 107 patients were reviewed retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
18
2
2
Order By: Relevance
“…As p53 is the most commonly mutated gene in human cancer, including lung squamous cell carcinoma, it has attracted a great deal of interest as a prognostic factor, diagnostic tool and therapeutic target [17]. Recent studies using immunohistochemical staining following antigen retrieval investigated the expression of p53 in 45 patients with non-small cell lung carcinomas and found that 40% of the tumors demonstrated positive of p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As p53 is the most commonly mutated gene in human cancer, including lung squamous cell carcinoma, it has attracted a great deal of interest as a prognostic factor, diagnostic tool and therapeutic target [17]. Recent studies using immunohistochemical staining following antigen retrieval investigated the expression of p53 in 45 patients with non-small cell lung carcinomas and found that 40% of the tumors demonstrated positive of p53.…”
Section: Discussionmentioning
confidence: 99%
“…The expression rate of altered p53 tumor suppressor gene was relatively high in small cell lung cancer (SCLC) without any prognostic significance [17].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bcl-2 overexpression, mainly with nuclear localization, together with a high Bcl-2/Bax ratio, was correlated directly with an elevated spontaneous apoptosis index (31)(32)(33), and with the absence of metastasis in SCLC tumors (34). The relationship between Bcl-2 overexpression and tumor stage is less clear, but an inverse correlation between Bcl-2 levels and cancer progression has already been pointed out (29,(34)(35)(36). In addition, there are cases of reduced Bcl-2 levels upon in vitro acquisition of resistance to cisplatin (37).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, despite controversial data, existing evidence about the specific role of Bcl-2 in SCLC is consistent with the results obtained in the present study. It has been demonstrated that, regardless of the frequently observed Bcl-2 overexpression in SCLC cell lines (2) and tumors (3), there is no correlation between Bcl-2 expression and resistance to therapy and/or patient survival (26)(27)(28)(29)(30). In fact, Bcl-2 overexpression, mainly with nuclear localization, together with a high Bcl-2/Bax ratio, was correlated directly with an elevated spontaneous apoptosis index (31)(32)(33), and with the absence of metastasis in SCLC tumors (34).…”
Section: Discussionmentioning
confidence: 99%
“…This high degree of variability of cell cycle components and their regulators in SCLC makes the predictions about response to cell cycledirected agents very complex. Almost 60% to 80% of the SCLC patients express abnormal p53 without any chemotherapy response correlation or prognostic significance (33) and in vitro, wild-type p53 restoration does not modify the sensitivity of a lung cancer cell line to a given chemotherapeutic agent (34). Flavopiridol is known to induce apoptosis in certain cell types independent of Rb and p53 pathway alterations (35,36).…”
Section: Discussionmentioning
confidence: 99%